REVEALING URBAN MARKETPLACE IDENTITY: PUDU - Ibrahim, Mohamad Asri; Wahab, Mohammad Hussaini; Mohmad Shukri, Sharyzee (PLANNING MALAYSIA, 2018)
The process of regenerating existing urban marketplaces should consider the components that make them special, as not to lose the delicate characters that give each marketplace distinctive identity and sense of place. This study focuses on identifying and evaluating urban marketplace by reviewing the definitions and concept of physical characters, and the experiential qualities of urban marketplace in Kuala Lumpur that contribute to the identity of a place. This study discovered that the marketplace physical surrounding and the activities that are happening are two of the elements which are associated with the place’s identity. This study concludes that urban marketplace physical and experiential quality can be regenerated to reveal an identity with strong sense of place.